2020
DOI: 10.1016/j.oooo.2020.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism of TNFRSF1 A may act as a predictor of severe radiation-induced oral mucositis and a prognosis factor in patients with head and neck cancer

Abstract: The aim of this study was to evaluate the relationship between single nucleotide polymorphism (SNP) (À135 T>C) of TNFRSF1 A and the frequency of occurrence and severity of oral mucositis (OM) in patients with head and neck cancer (HNC) treated with radiotherapy (RT). Study Design. This retrospective, cohort study included 60 patients with HNC treated with intensity-modulated radiation therapy (IMRT). TNFRSF1 A SNP analysis (À135 T>C) was performed by using molecular probes (TaqMan, ThermoFisher Scientific, Wal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…The TNF receptor, TNFR1, when activated, regulates an apoptotic pathway and may be involved in the development of mucositis. Two articles assessed SNPs in the promoter region of the gene encoding the receptor protein, TNFRSF1A, and showed a significant increase in the likelihood of grade 3 mucositis in the last weeks of RT in CC, TT, or GT genotype carriers [ 27 , 31 ]. The other article addressing the TNF pathway assessed the relationship between the SNP (-1211 T>C, rs1799964) in the TNF-α gene itself and the occurrence and intensity of OM [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The TNF receptor, TNFR1, when activated, regulates an apoptotic pathway and may be involved in the development of mucositis. Two articles assessed SNPs in the promoter region of the gene encoding the receptor protein, TNFRSF1A, and showed a significant increase in the likelihood of grade 3 mucositis in the last weeks of RT in CC, TT, or GT genotype carriers [ 27 , 31 ]. The other article addressing the TNF pathway assessed the relationship between the SNP (-1211 T>C, rs1799964) in the TNF-α gene itself and the occurrence and intensity of OM [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…In their work, Mlak et al (2020) showed that the CC genotype of the TNFRSF1 A gene is associated with a more severe course of OM [ 31 ]. The SNP identified in this study is located in the regulatory region of the TNFRSF1 A gene.…”
Section: Discussionmentioning
confidence: 99%
“…found that CSF1 overexpression after SARS-CoV-2 infection led to pulmonary fibrosis by promoting the recruitment and activation of macrophages ( 50 ). TNFRSF1A is a tumor necrosis factor receptor, and the interaction between tumor necrosis factor and TNFRSF1A plays an important role in inhibiting the occurrence of inflammation, tumor proliferation, migration, and invasion ( 52 ). Wilson et al.…”
Section: Discussionmentioning
confidence: 99%
“…Bertolazzi et al found that CSF1 overexpression after SARS-CoV-2 infection led to pulmonary fibrosis by promoting the recruitment and activation of macrophages (50). TNFRSF1A is a tumor necrosis factor receptor, and the interaction between tumor necrosis factor and TNFRSF1A plays an important role in inhibiting the occurrence of inflammation, tumor proliferation, migration, and invasion (52). Wilson et al found that TNFRSF1A induced alveolar epithelial cell dysfunction in the early stages of acute respiratory distress syndrome, which promotes lung permeability and inhibits the reabsorption of alveolar fluid (53).…”
Section: Discussionmentioning
confidence: 99%
“…Five studies were conducted on a small number of HNSCC patients receiving radiation therapy in the oncology department at the Medical University of Lublin (Lublin, Poland). They showed that polymorphisms in GHRL (rs1629816) [40], TNFRS1A [41] (rs4149570, rs767455) [42]), TNFA (rs1799964) [43], and APEH (rs4855883) [44] were significantly associated with OM. In a larger sample (n = 114) of Chinese patients with HNSCC receiving radiotherapy, Chen et al [45] found the XRCC1 variant (rs25487) to be associated with an increased risk of OM.…”
Section: Candidate-gene Studiesmentioning
confidence: 99%